DA'I COMMUNICATION MANAGEMENT IN THE NAHDLATUL ULAMA RECITATION GROUP IN BEKASI (KAJIAN AL QUR'AN SURAH ALI IMRAN AYAT 104) - Ahmad Soleh; Hadi Hidayat (EKOSSISTEM : Islamic Economics, Banking, Law, System, 2025)
The purpose of this study is to explore the management of Da'i communication in the Nahdatul Ulama recitation group in Bekasi based on Surah Ali Imran verse 104. The method used is a qualitative approach with literature study, including analysis of the text of the Qur'an and its interpretation to understand the context and meaning of the verse. Data collection is carried out through an in-depth study of the text. The results of the study show that the management of da'i communication in da'wah to the community is a complex process that requires planning, organizing, implementing and supervising communication as well as having listening skills, empathy, and understanding of verbal and non-verbal elements to create a harmonious relationship with the da'wah community. Good communication management skills not only help Da'i in preaching but also improve the ability to express themselves and understand others, and contribute to a collaborative social climate. This study also identifies how the communication management of a Da'i in dealing with group communication challenges such as resistance between group members due to lack of communication skills to convey and listen to messages from group members. The solution is that government support is needed such as contextual education and communication training for Da'i. Thus, investing in the communication management skills of a Da'i provides important benefits in achieving the broader goals of da'wah, creating an obedient, harmonious, and productive society.